10+(-5)+6=n

Simple and best practice solution for 10+(-5)+6=n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10+(-5)+6=n equation:


Simplifying
10 + (-5) + 6 = n
10 + -5 + 6 = n

Combine like terms: 10 + -5 = 5
5 + 6 = n

Combine like terms: 5 + 6 = 11
11 = n

Solving
11 = n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-1n' to each side of the equation.
11 + -1n = n + -1n

Combine like terms: n + -1n = 0
11 + -1n = 0

Add '-11' to each side of the equation.
11 + -11 + -1n = 0 + -11

Combine like terms: 11 + -11 = 0
0 + -1n = 0 + -11
-1n = 0 + -11

Combine like terms: 0 + -11 = -11
-1n = -11

Divide each side by '-1'.
n = 11

Simplifying
n = 11

See similar equations:

| F(6)=7x^2+8 | | x-c/2 | | 2w+6w-15=129 | | 12x-(2x-5)=16 | | a=-6+(-2)+(-1) | | 2x+4x-35=19+2+2x | | P=2175-2187.5(0.25) | | 4x-(3x-5)=3 | | 27x^6-35x^3+8=0 | | 2x-5/3=3/4(x-2) | | 2t-19+5t-20+2t-15=180 | | 21+[36(12-6)+2-5]3= | | 1=1/5y-7/10x=0 | | -8/5/6= | | 3x+4(2x-9)=52 | | 4(2x-5)=9(x-2) | | Y-4=1/7(x-3) | | 9b^2+9b-40=0 | | -3.6x=51.48 | | w+20+6w+6+4w=180 | | (5+z)(5z-1)=0 | | 42+12=30 | | 13a+14+6a= | | 2cos^2-cosx=1 | | 5x^2+12x+10=x^2+10x | | (2e^-4)-((5/7)e^-7)=x | | -7-8b=17 | | 3a^2-33ab+54b^2= | | 0.2(5-3)= | | 4u^2-20u=0 | | 9m-27=4m+1 | | (2e^-4)-((5/7)e^-7) |

Equations solver categories